Analgesic and anti-inflammatory effects of an extract of Fadogia agrestis in rats - Oyekunle, O.A.; Okojie, A.K.; Udoh, U.S. (Нейрофизиология, 2010)
Analgesic and anti-inflammatory activities of an aqueous extract produced from Fadogia agrestis (family Rubiaceae) stem bark were investigated using animal models. Знеболювальна й протизапальна активність водного екстракту, виготовленого з кори Fadogia agrestis (сімейство Маренові), вивчалася на щурах з використанням різних моделей болю та запалення.